Síndrome de Burnout na equipe de enfermagem em unidades de pronto atendimento - Lordão, Alana Vieira (2019)
Introduction: Burnout syndrome is a disease of the workplace and that every day affects more workers, bringing negative individual and collective repercussions. Article 1 - Scientific production of Nursing in Burnout Syndrome: bibliometric review. Objective: To verify the scientific production in Burnout Syndrome in Nursing from January 2000 to December 2018. Method: Bibliometric study. The Scopus and Web of Science databases were used. For the search of the articles we used the terms "Burnout" and "nursing", the data were recorded in Excel spreadsheet. Results: A total of 96 publications were raised since 2005, since there are productions every year with a peak in 2014 (14 articles). The Revista Latino Americana de Enfermagem presented more articles (19) in the period. Bradford's law concentrated 19 articles in a magazine in the nucleus; in the first area 27 articles in 2 journals; zone 2 had 24 articles in 8 journals and in area 3 it had 26 articles in 26 different journals. The most productive author was Professor Edineis Guirardello, with index h 10. Conclusion: It is an important study to guide the researcher in the research trends of the area. The limitations were presented in the sense of the registers not always being standardized. Article 2 - Burnout Syndrome in the Care Units of João Pessoa. Objective: To verify the presence of Burnout Syndrome in the Nursing professionals of the Emergency Care Units of the city of João Pessoa. Method: Field research performed with Nurses and Nursing Technicians. A sociodemographic instrument plus the Questionnaire for the Evaluation of the Quermarse por el Trabajo syndrome was used to identify the syndrome. Results: 37 (26.2%) Nurses and 104 (73.8%) Nursing Technicians participated in the study, most of them female (87.2%). All dimensions presented Cronbach's alpha greater than 0.70. Most professionals present average level of risk for burnout. 86% presented profile 1 and 14% profile 2 of burnout. Conclusion: Burnout syndrome represents a risk to the health worker, it is necessary to launch strategies for early diagnosis and follow-up of the professionals who are already in the field. 2 It is necessary to say that more research strengthens the argument of preventive measures for the mental health of the worker.